Cover crops reduce weed seedbanks in maizecassava systems in southwestern Nigeria - Ekeleme, F.; Akobundu, I.O.; Isichei, A.O.; Chikoye, David (Weed Science Society, 2003)
Weeds are a major constraint to crop production in smallholder farms in tropical Africa. The weed seedbank and annual recruitment are the main sources of weed infestation in crops. This study was carried out in Ibadan, Nigeria, to evaluate the effect on the seedbank of two types of planted fallow (alley cropping with leucaena and live mulch with tropical kudzu) and a natural bush fallow under four land-use intensities. Type of fallow was the main plot. Land-use intensities, consisting of continuous cropping of maize intercropped with cassava, 1 cropping yr of maize–cassava followed by 1, 2, and 3 yr of fallow, were the subplots. Averaged over a 3-yr period, the seedbank was 55% lower in the tropical kudzu plots and 43% lower in the leucaena plots compared with natural bush. The difference in seedbanks between plots cultivated after leucaena and natural fallow was 23%. Seed density of annual broadleaf weeds was high and dominated the seedbank of both planted and natural fallow. Overall, seeds of grasses occurred at low densities in all plots cultivated after 2 to 3 yr of fallow, whereas seeds of sedges occurred more in continuously cultivated plots and plots cultivated after 1 yr of fallow in all the fallow types. Seed density of perennial broadleaf weeds increased as land-use intensity decreased. Live mulch with tropical kudzu, especially when combined with 2 to 3 yr of fallow, lowered the seedbank more than the leucaena and traditional bush fallow systems.